PEMBATASAN TRANSFER DAYA MAKSIMUM DAN PEMASANGAN KAPASITOR UNTUK STABILISASI TEGANGAN - Qeis Irdha; Maula Sukmawidjaja (Website, 2017)
This article discusses about the maximum power transfer limitation and capacitor installation to maintain voltage stability at South and Central Kalimantan 150 kV Substation, so that the voltage stability can be maintained and voltage collapse can be anticipated. Based on analysis result using power and voltages relation curve, the system is still in a reliable condition. At off-peak times, Bangkanai substation will collapse when power transfer reaches 138.079 MW, while Cempaka and Trisakti substation can attain until they reach 175.392 MW and 171.576 MW respectively. Simulation result, using DIgSILENT software shows, at peak load, Bangkanai, Cempaka and Trisakti substation will collapse when the power transfer reach 214.430 MW, 175.966 MW and 171.576 MW respectively. When Cempaka substation reaches the maximum power transfer, the capacitor which has 49.92 MVAR reactive power was installed and the voltage of that substation was improved from 0.958 pu to 0.980 pu. Key Words : voltage stability, drop voltage, voltage collapse, DIgSILENT, locus of critical operation point. ABSTRAKPenelitian ini membahas tentang pembatasan transfer daya maksimum dan pemasangan kapasitor untuk menjaga stabilitas tegangan pada GI 150 kV di Kalimantan Selatan dan Tengah sehingga stabilitas tegangan dapat dijaga dan runtuh tegangan dapat diantisipasi. Berdasarkan hasil analisis menggunakan kurva hubungan daya dan tegangan, sistem masih dalam kondisi yang handal. Di luar waktu beban puncak, GI Bangkanai runtuh ketika transfer daya mencapai 138,079 MW, sedangkan GI Cempaka dan GI Trisakti runtuh ketika transfer daya mencapai masing-masing 175,392 MW dan 168,572 MW. Hasil simulasi menggunakan software DIgSILENT, ketika waktu beban puncak, GI Bangkanai , GI Cempaka dan GI Trisakti masing-masing runtuh ketika transfer daya mencapai 214,430 MW, 175,966 MW, dan 171,576 MW. Ketika GI Cempaka mencapai transfer daya maksimumnya, dilakukan pemasangan kapasitor yang memiliki daya reaktif sebesar 49,92 MVAR. dan tegangan pada GI tersebut membaik dari 0,958 pu menjadi 0,980 pu.Kata kunci: stabilitas tegangan, jatuh tegangan, runtuh tegangan, DIgSILENT, titik operasi kritis.